FORTIFICATION EFFECT OF CRAB (Portunus pelagicus) SHELL FLOUR ON CONSUMER ACCEPTANCE OF SAGO CRACKERS - Sari, Wulan Puspita; ', Dewita; ', Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was aimed to determine the fortification effect of crab (portunus pelagicus) shell flour on consumer acceptance of sago crackers. This researh was conducted in fishery product technology and fishery product chemistry laboratorium Faculty of Fisheries and Marine Science Universitas Riau on Mei to June 2016. The methode used in this research was experimental methode by using crab (portunus pelagicus) shell flour on processing of sago crackers. The concentration of crab shell was 0 gr, 15 gr, 30 gr, and 45 gr. The result showed that effect of fortification 15 gr of crab shell flour (X1) was the best treatment based on organoleptic value with flavour 2.96, appearance 2.72, aroma 2.61, texture 3.56 and flower power 149.13%. Meanwhile effect of fortification 30 gr of crab shell flour (X2) was the best treatment based on chemical analysis with protein content 5.13%, water content 9.42%, ash content 13.37% and calsium content 17.01%.Keywords : Sago, Crab Shells, Sago Crackers